Synthesis and Structural Characterization of N-Hydroxy-7-oxa-bicyclo[2,2,1]hept-5-ene-2,3-dicarboximide - Li, Jian (Asian Journal of Chemistry, 2012)
The compound N-hydroxy-7-oxa-bicyclo[2,2,1]hept-5-ene-2,3-dicarboximide (C8H7NO4, Mr = 181.15) was synthesized and characterized by elemental analysis, 1H NMR spectra, IR spectra and single crystal X-ray diffraction. The crystal belongs to orthorhombic, space group Pnma, with a = 10.9505(11), b = 10.7263(10), c = 6.4005(4) Å, b = 90.00º, V = 751.79(11) Å3, Z = 4, Dc = 1.600 g/cm3, l = 0.71073 Å, μ(MoKa) = 0.131 mm-1, F(000) = 376. The final refinement gave R = 0.0434, wR(F2) = 0.1074 for 702 observed reflections with I > 2s(I). The structure of the title compound comprises a racemic mixture of chiral molecules containing four stereogenic centres. X-Ray diffraction analysis reveals that the cyclohexane ring tends towards a boat conformation, the tetrahydrofuran ring and the dihydrofuran ring adopt envelope conformations.